2005 IEEE Conference on Emerging Technologies and Factory Automation
DOI: 10.1109/etfa.2005.1612555
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PROFIBUS Networks Using a Fault Injection Framework

Abstract: Industrial control systems architectures have been evolving to the decentralization of control tasks. This evolution associated with the time-critical nature of these tasks, increases the dependability requirements for one of their most critical components: the communication system. Therefore, this is an important aspect on the control system design which must be properly evaluated. In this paper the dependability of a PROFIBUS network is assessed. By using of a fault injection framework the network operation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Os trabalhos mais próximos do relatado aqui são injetores de falhas para redes de controle. Fault Injection Framework for PROFIBUS, uma rede de campo que suporta PROFIsafe, é um framework de injeção de falhas desenvolvido para avaliar o PROFIBUS (Carvalho, Carvalho, and Portugal 2005). Seu principal objetivo é analisar o comportamento do PROFIBUS na ocorrência de falhas e também a interferência dos mecanismos de tolerância a falhas no desempenho do protocolo.…”
Section: Injeção De Falhas E Trabalhos Relacionadosunclassified
“…Os trabalhos mais próximos do relatado aqui são injetores de falhas para redes de controle. Fault Injection Framework for PROFIBUS, uma rede de campo que suporta PROFIsafe, é um framework de injeção de falhas desenvolvido para avaliar o PROFIBUS (Carvalho, Carvalho, and Portugal 2005). Seu principal objetivo é analisar o comportamento do PROFIBUS na ocorrência de falhas e também a interferência dos mecanismos de tolerância a falhas no desempenho do protocolo.…”
Section: Injeção De Falhas E Trabalhos Relacionadosunclassified
“…In [2][3], master-slave based polling protocols are proposed, the authors use a different channel for retransmission. However, in [4] [5], it is shown that there will be serious issues of unstability if the token frames are lost. A well known solution for industrial wireless automation is WirelessHart [6] [7], which supports mesh networks and TDMA based scheduling.…”
Section: Introductionmentioning
confidence: 99%
“…In [49], the adaptive-intervals MAC protocol has been proposed that uses a polling-based approach combined with group testing feature for improving the delay in low load conditions. However, in [7,22], the authors show the serious stability issues due to the loss of token frames leading to unsatisfying real-time performance arising from running the existing PROFIBUS MAC and link-layer token-passing master-slave protocols over an 802.11 DSSS PHY. Works such as [39] where the authors propose schemes to support combined periodic and aperiodic traffic over Bluetooth networks, [44] where the authors propose the use of DSSS CDMA technology to build Industrial Control WLAN for enhanced robustness, and [32,35,30] which propose extensions for a wireless fieldbus network also fall into the category of using existing standardized protocols for real-time communication over wireless networks.…”
Section: Inadequacies Of Existing Wireless Standardsmentioning
confidence: 99%